Art therapy in art museums: Promoting social connectedness and psychological well-being of older adults. (July 2016) - Bennington, Rose; Backos, Amy; Harrison, Jennifer; Etherington Reader, Arnell; Carolan, Richard
Highlights: We examine the use of the art museum as a therapeutic tool with older adults. The art museum provided a safe exploration of emotions, thoughts, and memories. Qualitative data revealed increased well-being and social connections. This study supports previous research on the therapeutic value of art museums. Abstract: This study aimed to identify the therapeutic benefits of utilizing the art museum, in art therapy programs, with older adults. Eight older adults participated in docent tours with an art making component at the [BLINDED FOR REVIEW] Museum in California. This study explored the phenomenological perspective of the older adults visiting the museum and aimed to understand how the experience may have impacted their well-being and sense of social support. Participant's art, journals, and researcher's observations were analyzed along with measures of psychological well-being, social connectedness and support. Emergent themes in the art and writing were aligned with De Botton and Armstrong's (2013) seven functions of art. Results indicated the opportunity to explore emotions, thoughts, and memories safely within a group increased participant's well-being and allowed for social connections. Furthermore, the art created reflected the seven functions of art, suggesting these may be useful for the layperson when visiting museums. This study supports previous research, recommending museum visits and art therapy with older adults.